Rekondisi Mesin Bubut DoALL LT 13 BU01 Di Laboratorium Mekanik Politeknik Manufaktur Negeri Bangka Belitung - Fajar Aswin; Masdani Masdani; Randa Randa; Otniel Yulianto (Manutech : Jurnal Teknologi Manufaktur, 2017)
This paper discusses the process of restoring the original condition (recondition) of DoAll LT 13 Bu01 by focusing on electrical system improvements, geometric precision and machine performance. Direct observation methods are applied to solve problems that include cause and effect relationships using 5 (five) why analyzes. The reconditioning stage starts from the initial data collection of damage obtained by visual inspection, function testing and geometric testing on the machine; then proceed with analyzing the damage; and corrective actions based on the results of the analysis. Functional testing methods, geometric deviation tests, machine performance tests are performed to see the achievement of recondition goals. Based on the results of the tests performed, the function of the electrical system returned to normal, the average value of geometric deviation still satisfied based on ISO-1708 standard and machine performance for spindle rotation value with 5% deviation, the value of the roundness and taper work-piece results of 0 and 0.004mm / 255mm, respectively and spindle vibration in the range of 0.33 - 0.66 mm / s RMS for speed 50 - 2500 RPM is still considered normal based on ISO 10816 standards.